2020
DOI: 10.1097/mnm.0000000000001169
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative F-18-FDG PET/computed tomography parameters for prediction of grade in patients with renal cell carcinoma and the incremental value of diuretics

Abstract: Objective The primary objective of the study was to evaluate the correlation between semi-quantitative F-18 FDG PET parameters and renal cell carcinoma (RCC) grade and its role in predicting the histopathological grade in RCC. The secondary objective was to evaluate the role of forced diuresis in improving the diagnostic accuracy of F-18 FDG for RCC. Methods Thirty-three patients with radiologically proven RCC were included in the study. All patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…But this does not mean that PET/CT examination is useless for the diagnosis of ccRCC. A number of studies have shown that the value of maximum standardized uptake value (SUVmax) as the traditional PET/ CT parameter has a certain correlation with the Fuhrman grade of pathology [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…But this does not mean that PET/CT examination is useless for the diagnosis of ccRCC. A number of studies have shown that the value of maximum standardized uptake value (SUVmax) as the traditional PET/ CT parameter has a certain correlation with the Fuhrman grade of pathology [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that high 18 F-FDG uptake in RCCs is associated with high ISUP grades 30 . In addition to ISUP grade, LVI has been added as a new prognostic factor for cancer-specific survival and metastasis-free survival in RCC cases 29 .…”
Section: Discussionmentioning
confidence: 91%
“…Seven days after the G. parasuis SH0165 challenge, the brains and lungs of the surviving piglets from all groups were isolated, fixed in 10% neutral-buffered formalin, and embedded in paraffin. Tissue sections (4 μm thick) were stained with haematoxylin and eosin with the standard method and observed with light microscopy [ 25 ].…”
Section: Methodsmentioning
confidence: 99%